Study on the function of TTG1 gene in Camellia oleifera - Xiang, Chengcheng; Xiao, Lizhi; Tao, Hongmei; Cao, Jie; Yuan, Jun; Wang, Weihao; Jiang, Yao (Frontiers in Plant Science, 2025)
Camellia oleifera is an economically important woody oil crop in China, where seed oil quality and yield are critical determinants of commercial value. Although the WD40-repeat transcription factor TTG1 is known to regulate plant secondary metabolism and development, its specific functions in C. oleifera remain uncharacterized. In this study, we isolated the CoTTG1 gene from C. oleifera, which encodes a nuclear-localized protein (molecular weight 38.38 kDa, pI 5.0) sharing 99.71% sequence identity with Camellia japonica TTG1. Heterologous expression resulted in: (1) significantly increased leaf trichome density (up to 114 trichomes/50 mm²); (2) enhanced seed anthocyanin accumulation (199–318% increase); and (3) substantial alterations in fatty acid composition, including 79% elevation in oleic acid (C18:1), 113% increase in gondoic acid (C20:1), 35% reduction in both linolenic (C18:3) and palmitic acids (C16:0), and 87% decrease in erucic acid (C22:1). Molecular analyses revealed that CoTTG1 mediates these phenotypic changes through upregulation of trichome development-related genes (AtETC1, AtGL1, AtCPC), anthocyanin biosynthesis genes (AtF3’H, AtLDOX, AtUFGT), and lipid metabolism genes (AtLACS8, AtSAD). These findings demonstrate the pleiotropic regulatory roles of CoTTG1 in controlling key agronomic traits, establishing it as a valuable molecular target for genetic improvement of C. oleifera.